Funcionamiento familiar, comportamientos internalizados y externalizados en un grupo de adolescentes (2017)
With this correlational study based on a quantitative approach, it is adapted to the relationship of the dimensions of cohesion and flexibility (familiarity), with the internal and external behaviors of the self-report of YSR. This is proposed to know the relationship between these two constructs. The sample is made up of teenagers, tenth grade students (10) and eleventh (11) (Colombian higschool) of a Public Institution from Bogotá. The correlation between the results of the Family Functioning Scale FACES III (Olson, 2000, Olson, Russell and Sprenkle, 1989), and the behaviors evaluated by the Youth Self-Report (YSR) (Achenbach Edelbrock and Howell 1987). For this reason, a descriptive analysis of the sociodemographic variables has been carried out in order to characterize the sample; semans frequency analysis of family typologies, of internalizing and externalizing behaviors. Likewise, the correlations between the dimensions of family functioning and the internalized and externalized behaviors were calculated. The purpose is to measure and analyze the dimensions in which students are located, both at the behavioral and family level; due to this, the theoretical revision of concepts such as family, family types, internal and external behaviors, in teenagers and regarding the theoretical content has been taken into account. Other authors and ideas of theories have also been taken into account in order to deepen the subject.